PREPARATION OF REPORTS FOR THE FIRST TIME ACCORDING TO INTERNATIONAL STANDARDS OF FINANCIAL REPORTING - Kudbiyev , Davlatbay; Mamarasulov , Diyorbek Alijon ugli (Innovative Development in Educational Activities, 2024)
Currently, the number of companies is increasing to start preparing reports in accordance with the requirements of the decision PQ-4611 at February 24 2020, "On additional measures for the transition to international standards of financial reporting" of the President of the Republic of Uzbekistan. This decision requires companies to prepare reports based on the norms of several laws and the requirements of report users (banks, stock exchanges, shareholders). Of course, these requirements reflect the importance of the difficulties in preparing reports on the IFRS. The preparation of the first report on the IFRS is a difficult task and requires considerable resources. In order to avoid excessive spending of these financial and moral resources, it is necessary to have sufficient knowledge and practice to prepare a report according to international standards.